La influencia del producto, precio y promoción en la decisión de compra de smartphones en las mujeres millennials de Lima Metropolitana - Trujillo Rivas, Isabel Franchesca (2020)
In this research work, three variables were evaluated within the Marketing mix: the product, price and promotion in the behavior of buying Smartphones in millennial women living in Lima Metropolitana. And, that is because technology and the demand of new products in the electronic consumer industry is growing and led us to investigate the factors that influence the purchase decision of these new consumers called “millennials”. According to a study carried out by CPI (2019), there is a higher consumer demand through the internet by woman by 5% higher than men in Peru. Therefore, millennial woman are the target market in the consumer electronics industry